CUSTOMER PERCEPTION OF SERVICES QUALITY OF THE ISLAMIC BANKING IN MALAYSIA DURING COVID-19 PANDEMIC - Uddin, Md. Kamal; Bhuiyan, Abul Bashar; Kumar, Dhanonjoy; Haque, Tasnuba; Sahabuddin, Mohammad (International Journal of Business and Management Future, 2022)
The aims of this study is to explore the factors that affect customers’ satisfaction with Islamic banking services in Malaysia during Covid-19 pandemic. The study is basically conducted on the basis of primary data collected by a well-structured questionnaire using Google Form. The respondents were 102 customers of Islamic Banking in Malaysia by using a simple random sampling technique. Both descriptive and inferential statistics have been used in the study. Descriptive statistics include percentage, mean, standard deviation and inferential statistics include, Reliability test, ANOVA, and Multiple Regression analysis. Regression analysis applies to find the casual effect relationship between dependent and independent variables. The study results show that reliability, competence, and service quality have a positive and significant relationship with customer satisfaction except transparency. The study reveals that reliability, competence, and service quality significantly affect customer satisfaction of Islamic banking services during Covid-19 pandemic but transparency has no effects on satisfaction during the pandemic situation. The study emphasizes that the Islamic banking institutions in Malaysia should focus the reliability and competency to enhance the quality of services during the crisis periods and to meet the customers’ expectations which led to customer loyalty. JEL Classification Codes: G20.